Mining Industry. - Maksarov, Vyacheslav V. (Trans Tech Publications, Limited, 2022)
Selected peer-reviewed full text papers from the 9th International Scientific Conference on Innovations and Prospects of Development of Mining Machinery and Electrical Engineering (IPDME 2021).
Description based upon print version of record.
Keywords: Mineral industries.; Mines -- Industrie.; mining.; Mineral industries